Dynamics of Political Participation of Women in Iran: A Factual Review - Hamzeh, Farhad (International Journal of Bio-resource and Stress Management, 2010)
Political participation means taking part in politics. The general level of participation in a society is the extent to which the people as a whole are active in politics: the number of active people multiplied by the amount of their action, to put it arithmetically. Perhaps the most remarkable political development of the 20th century is the global spread of democracy. The increasingly important role of election in regional, national and world level, has obtained it as a basic political topic. Iran has repeated the experience of democracy several times. The Islamic Consultative Assembly election is one of the most important political events in Iran which holds once in every 4 years. The main aim of this research is to evaluate the role of women in parliament of Iran (1st to 7th round) through participation in the Islamic Consultative Assembly elections. Parliamentary election of Iran is a developing and active process. This paper concentrates on the process of changing and growing rates of women’s participation in the political affairs of Iran.